Islam and State Institutions: Islam dan Lembaga Negara - Dewi Sukmawati; Galuh Pajar Pratama; Davi Abdulloh Haidzam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Abstract Indonesia has a well-organized institutional framework, especially in a democratic context that prioritizes citizens' rights. An ideal democratic country is one that gives supreme power to its people, has responsible citizens, a government that is managed by the people, and authority that is exercised by the people. The approach in this context refers to the point of view used by a researcher to examine data from the literature interpretation. Choosing a particular approach or point of view in a research really depends on the research question you want to answer. In this research, the method applied is an interpretive approach, namely an approach that allows researchers to interpret interpretive texts or literature with the aim of providing an explanation of the content of the interpretation being studied. Janedjri stated that every position established by law can be called an instrument of the state, The meaning also refers to humans who carry out functions or positions in activities within the framework of the state. This meaning goes beyond the physical structure of state institutions. However, if interpreted strictly, state institutions are institutions that have a certain legal status determined by the Constitution. The state is an abstract entity that is realized in its totality. Surah Ibrahim verse 35 and Saba verse 15 relate to the regulation of government institutions in the Maudhu'i system. Based on the interpretations of several scholars, the conclusion can be drawn that a safe country is one inhabited by individuals who always remember Allah and ask Him for forgiveness.